Harnessing the Ecological and Genomic Adaptability of the Bacterial Genus Massilia for Environmental and Industrial Applications - Kamyar Amirhosseini; Mehrdad Alizadeh; Hamed Azarbad (Microbial Biotechnology)
ABSTRACT The bacterial genus Massilia was first described in 1998, and since then has attracted growing interest due to its ecological plasticity and biotechnological promise. Certain species of the genus Massilia inhabit a variety of ecosystems, from arid deserts to polar glaciers, and exhibit unique adaptations such as resistance to cold and heat. In contaminated environments, some members of Massilia contribute significantly to the detoxification of heavy metals and the degradation of organic pollutants, presenting them as promising agents for bioremediation. In addition, Massilia species improve plant resistance and facilitate pollutant absorption in phytoremediation strategies. New research also highlights their potential as bioindicators of environmental health, given their abundance in anthropogenically influenced ecosystems and airborne microbial communities. In addition to their ecological roles, some Massilia species have potential in biotechnological applications by producing biopolymers and secondary metabolites. Here, we integrate findings across various habitats to present a comprehensive overview of the ecological and biotechnological importance of the genus Massilia. We highlight critical knowledge gaps and propose future research directions to fully harness the potential of this not fully explored bacterial genus to address environmental challenges, including contamination.